2004
DOI: 10.1161/01.res.0000133678.22968.e3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cardiac Nerve Sprouting After Myocardial Infarction in Dogs

Abstract: Abstract-Cardiac nerve sprouting and sympathetic hyperinnervation after myocardial infarction (MI) both contribute to arrhythmogenesis and sudden death. However, the mechanisms responsible for nerve sprouting after MI are unclear. The expression of nerve growth factor (NGF), growth associated protein 43 (GAP43), and other nerve markers were studied at the infarcted site, the noninfarcted left ventricle free wall (LVFW), and the left stellate ganglion (LSG) at several time points (30 minutes to 1 month) after M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
301
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(331 citation statements)
references
References 32 publications
29
301
0
1
Order By: Relevance
“…Previous studies in dogs showed that NGF protein increases by 7 days post-infarct, and returns to lower levels by 1 month (Zhou, et al, 2004), temporally paralleling changes in peri-infarct sympathetic innervation. Using a rodent model, we show here that i) both NGF mRNA and protein increase in the peri-infarct zone with a time course similar to increased protein reported for canines; ii) the time frame for increased NGF mRNA and protein parallels macrophage and myofibroblast emigration into the peri-infarct; iii) NGF protein and mRNA is localized primarily within peri-infarct macrophages and myofibroblasts, and iv) peri-infarct regions containing NGF-producing inflammatory cells are preferentially hyperinnervated.…”
Section: Cardiac Sympathetic Hyperinnervation As Sequela Of the Inflamentioning
confidence: 87%
See 2 more Smart Citations
“…Previous studies in dogs showed that NGF protein increases by 7 days post-infarct, and returns to lower levels by 1 month (Zhou, et al, 2004), temporally paralleling changes in peri-infarct sympathetic innervation. Using a rodent model, we show here that i) both NGF mRNA and protein increase in the peri-infarct zone with a time course similar to increased protein reported for canines; ii) the time frame for increased NGF mRNA and protein parallels macrophage and myofibroblast emigration into the peri-infarct; iii) NGF protein and mRNA is localized primarily within peri-infarct macrophages and myofibroblasts, and iv) peri-infarct regions containing NGF-producing inflammatory cells are preferentially hyperinnervated.…”
Section: Cardiac Sympathetic Hyperinnervation As Sequela Of the Inflamentioning
confidence: 87%
“…Postmortem analyses of infarcted human myocardium show abnormal increases in numbers of sympathetic axons adjacent to the site of injury (Cao, et al, 2000a). Ischemic injury appears to be the cause of the remodeling, as coronary artery ligation induces hyperinnervation in dogs (Lai, et al, 2000;Zhou, et al, 2004) and rats (Ahonen, et al, 1975;Paessens and Borchard, 1980;Holmgren, et al, 1981;Vracko, et al, 1990;Kaye, et al, 2000;Li, et al, 2004). Through enhanced norepinephrine-mediated myocardial depolarization, abnormally increased sympathetic nerve density may be proarrhythmogenic and represent a significant factor in post-infarct sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early rise of NGF can be observed rapidly after myocardial infarction (hours) and may possibly reflect an early rescue response to support myocardial healing (Meloni et al 2010). Unfortunately, NGF also causes inhomogeneity of sympathetic innervation in the infarction border zone thereby promoting lethal arrhythmias (Zhou et al 2004). Months later, if heart failure develops after MI, the opposite is detected and NGF tissue levels decrease below the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NGF and GAP 3 levels increased in the left stellate ganglion of these dogs 3 days after MI, without a concomitant increase in mRNA, indicating possible retrograde transportation of these proteins to the left stellate ganglion, which then triggers nerve sprouting in noninfarcted left ventricular sites. 48 Further evidence that sympathetic nerve sprouting is arrhythmogenic stems from studies of hypercholesterolemic rabbits compared with normal controls. Rabbits fed a high-cholesterol diet for 8 weeks had significantly higher densities of growth-associated protein 43 (a protein associated with axonal growth cone) and tyrosine hydroxylase, indicating nerve sprouting and sympathetic hyperinnervation.…”
Section: Myocardial Infarction Heart Failure and Sympathetic Innervmentioning
confidence: 99%